Diversity of vascular plants in Pu Luong nature reserve, Thanh Hoa province - Thin, Dau Ba; Ban, Pham Hong; Thin, Nguyen Nghia (Academia Journal of Biology, 2013)
Six surveys were conducted and all vascular plants were collected in Pu Luong Nature Reserve, from January 2010 to January 2013. The paper reported 1.459 species, 678 genera and 181 families of the 6 divisions. In Pu Luong Nature Reserve there are 50 threatened species listed in the Red Book of Vietnam 2007 and 24 species in Decree 32/2006/ND-CP by Government. The number of useful plant species of the Pu Luong flora is categorized as follows: 705 species for medicinal plants, 188 species for timber plants, 161 species for edible and 57 species for other. The plant species in Pu Luong mainly comprise the tropical elements (68.40%) of them, the endemic elements with 23.65%. The Spectrum of Biology (SB) of the flora in Pu Luong is summarized as follows: SB = 83.62 Ph + 8.50 Ch + 2.88 Hm + 1.78 Cr + 3.22 Th.